Effect of Growth Regulators and Seasons on the Propagation of Different Seabuckthorn Species Through Cuttings in Cold Deserts of Himachal Pradesh - Sankhyan, H. P.; Sehgal, R. N.; Bhrot, N. P. (Indian Forester, 2003)
No abstract